IMPROVING THE PERFORMANCE OF FOOD MSMES: A CASE STUDY ON HALAL TOURISM - Yuliana, Ika; Rahmatullah, Arwin Yafi; Ramdani, Rizal; Wardi, Putri Amalia; Makiah, Makiah (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
The number of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia continues to increase from year to year, including in Lombok, which is known as a leading halal tourist destination. Food MSMEs have a strategic role in supporting the development of halal tourism, but they face increasingly fierce competition. In this context, marketing communication strategies, Islamic financial literacy, and the use of digital technology are important factors in improving MSME performance. This study aims to analyze the influence of marketing communication and Islamic financial literacy on the performance of food MSMEs in Lombok, as well as to examine the role of digital technology as a moderating variable. The study uses a quantitative method with a causal approach, involving 108 respondents who are owners of food SMEs that have been operating for at least one year. Data analysis was performed using the Partial Least Squares (PLS) method. The results show that marketing communication and digital technology have a positive and significant effect on SME performance, while Islamic financial literacy does not have a significant effect. Furthermore, digital technology was not proven to play a role as a moderating variable between marketing communication and Islamic financial literacy on MSME performance. These findings emphasize the need to strengthen marketing communication strategies and optimize digital technology in supporting the competitiveness of halal tourism-based food MSMEs in Lombok, with recommendations for further research to expand the scope of the region and consider policy factors, training, and digital infrastructure.